Effect of dietary vitamin C on growth, reproduction and leucocyte counts in the gold fish, Carassius auratus (Linnaeus, 1758) - James, R.; Vasudhevan, I. (Indian Journal of Fisheries, 2011)
Effect of different levels of dietary vitamin C (0, 50, 100, 200 and 300 mg kg diet-1) on the growth, gonad weight, fecundity and leucocyte counts in gold fish, Carassius auratus were studied for a period of 120 days. Fish fed with 200 mg vitamin C kg diet-1 exhibited higher feeding and growth parameters than those fed with other vitamin C diets. The vitamin C contents of muscle and gonad increased with increase in vitamin C level in diet and muscle elicited three times more vitamin C content than gonad tissues. However, vitamin C content did not vary significantly (p>0.05) in both tissues during pre- and post-spawning periods. Female C. auratus fed on 100 and 200 mg vitamin C kg diet-1 began to develop gonad on day 40 and attained spawning stage on day 100 while fish fed on 0, 50 and 300 mg vitamin C kg diet-1 began to develop gonad on day 60 and attained the spawning stage on day 120, 100 and 100 respectively. Fish fed with 200 mg vitamin C kg diet-1 (p<0.05) had significantly heavier gonad, gonadosomatic index which inturn increased egg production and hatchability. The egg (weight and diameter) and larval (length and weight) qualities were significantly (p<0.05) higher in fish fed 200 mg vitamin C kg diet-1 as compared to other groups. Lymphocyte and monocyte populations were also high in these fish. Based on the results of the present study, 200 mg vitamin C kg diet-1 can be considered as the optimum dietary level to enhance growth, reproduction and immune response in gold fish, C. auratus. The probable mechanism of action of vitamin C on growth and reproduction is discussed.